The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3164/jcbn.17-105
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in LDL- and HDL-cholesterol subfractions in patients after the acute ischemic stroke and their association with oxidative stress markers

Abstract: The aim of our study was to examine gender differences of LDL- and HDL-cholesterol subfractions in patients after the acute ischemic stroke with focus on small LDL and HDL subfractions, and their association with oxidative stress markers. In addition, we have monitored the 7-day effect of cholesterol-lowering drugs administered to patients after the acute ischemic stroke, on these subfractions. Eighty two stroke patients and 81 age matched controls were included in this study. Blood was collected from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
(18 reference statements)
2
7
0
1
Order By: Relevance
“…After 50 years, cholesterol levels in men tend to continue to grow. 22 This is consistent with the study results, although the number of men but the mean cholesterol level of men was higher by a difference of 17.47 mg/dl. Statistically, there was no relationship between gender and cholesterol levels in respondents (p=0.883), supporting previous studies with the results that there was no relationship between sex and cholesterol levels (p=0.847).…”
Section: Effects Of Red Dragon Fruit On Cholesterolsupporting
confidence: 92%
“…After 50 years, cholesterol levels in men tend to continue to grow. 22 This is consistent with the study results, although the number of men but the mean cholesterol level of men was higher by a difference of 17.47 mg/dl. Statistically, there was no relationship between gender and cholesterol levels in respondents (p=0.883), supporting previous studies with the results that there was no relationship between sex and cholesterol levels (p=0.847).…”
Section: Effects Of Red Dragon Fruit On Cholesterolsupporting
confidence: 92%
“…To interpret these findings, further studies including fecal metabolome analysis should be necessary. However, of the 32 pathways, lipid metabolism seems of note, because Žitňanová et al (17) recently reported that subfractions of plasma lipid were significantly altered in acute phase of stroke, another limitation was that we did not adjust background factors to compare gut microbiota between groups. Previous report showed that several changes in gut microbiota were associated with age and sex, by analyzing 277 healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding that this study of middle-aged and older adults is the largest application of a HDLperox assay to date, and a number of unique findings were generated, there were also limitations. It should be acknowledged that the origins and consequences of gender and race-related differences in physiology and disease are multifactorial [ 34 ]. The current analysis did not consider many lifestyle variables and health care practices that can influence lipid metabolism and function, including diet, smoking, alcohol consumption and physical activity.…”
Section: Discussionmentioning
confidence: 99%